Dynamic Adjustment Towards Target Capital Adequacy Ratio: Evidence from Indian Commercial Banks. Issue 3 (June 2019) - Mohanty, Seba; Mahakud, Jitendra
Capital adequacy ratio (CAR) is one of the major indicators of the stability of the commercial banks. Pertinent to its pervasive importance, over the years, the regulators and policymakers focused on the maintenance of the particular level of capital ratio (CR) to minimize the solvency and liquidation risk. In this context, the purpose of this study is to estimate the speed of adjustment to the target CR of commercial banks in India. This study specifies the dynamic panel data model and more specifically generalized method of moments to find out the speed of adjustment by using the data span of 18 years, that is, from 1997 to 2014. We find that the speed of adjustment towards the target CR is around 39 per cent for all banks as a whole, which validates the fact that commercial banks operating in India do have the target CAR and they adjust their CRs to achieve this. The speed of adjustment to target CAR varies across the banks categorized on the basis of the ownership. The adjustment speed is more in case of public sector banks than the private and foreign banks. The results reveal that bank-specific variables like size, non-performing asset, net interest margin, leverage, loan to asset ratio and regulatory pressure determine the target CAR of the commercial banks in India.